Automated Scoring for Four-Tier Diagnostic Tests in Physics: A Systematic Review and Needs Analysis - Kania Fatikasari; Asrial Asrial; Tugiyo Aminoto; Tanti Tanti (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to establish an empirical foundation for developing an automated scoring system for four-tier diagnostic tests in physics education by mapping current research on tiered diagnostic instruments and identifying the practical scoring challenges teachers face in classroom misconception assessment. Methodology: A two-phase sequential design was used. A systematic literature review followed the PRISMA protocol across Scopus, ScienceDirect, and Google Scholar (compiled in Mendeley), with record screening managed in Rayyan and narrative synthesis of the selected studies, complemented by semi-structured interviews with four junior high school science teachers, analyzed thematically. Main Findings: Of 87 four-tier diagnostic studies, only 12 (13.8%) incorporated digital or automated elements, and most digital systems functioned merely as test-delivery platforms while misconception analysis remained manual. Interviews confirmed four recurring barriers: a heavy manual scoring burden, delayed feedback, difficulty distinguishing genuine understanding from guessing, and the need for a simple and accessible automated system. Teachers consistently requested a simple system generating immediate diagnostic results and misconception classifications. Novelty/Originality of this study: Unlike prior reviews that emphasize instrument construction, this study integrates systematic review evidence with concrete teacher needs to justify an accessible, low-tech automated scoring system built on Google Forms and Google Sheets, reframing the central barrier of four-tier assessment as scoring complexity rather than instrument design.